Development of RP-HPLC Method for Simultaneous Determination of Triclabendazole and Ivermectin in Pharmaceutical Suspension Dosage Form - Taj Ur Rahman; Ajmal Zaman; Ali Bahadur; Muhammad Aurang Zeb; Wajiha Liaqat; Eman Y. Santali; Sarah Alharthi; Ruwida M. K. Omar; Saif A. Alharthy; Ashraf Ali (Journal of Analytical Methods in Chemistry)
A reversed-phase high-performance liquid chromatography (RP-HPLC) method was developed for simultaneous determination of triclabendazole (TCB) and ivermectin (IVM) in pharmaceutical dosage form. A mobile phase consisting of acetonitrile/water (50:50 v/v) with a flow rate of 1.5 mL/min was used for chromatographic separation of the mixture of TCB and IVM. The developed method was found to be linear with the correlation coefficient (r = 0.999) for TCB and IVM in the presence of suspension. The limit of quantitation (LOQ), robustness, specificity, accuracy, and precision were validated for the developed method. The peak areas of five replicates of the samples were recorded, and the acceptance rate of suspension recovery was 98%. The intraday accuracies for TCB and IVM were 98.71% and 100.79%, respectively, with a relative standard deviation (RSD) of 0.87%. The limits of detection (LOD) of TCB and IVM were 0.058 mg/mL and 0.112 μg/mL, respectively, while the LOQ of TCB and IVM were 0.178 μg/mL and 0.340 μg/mL, respectively. The method’s % RSD for intra- and interday precision was deemed satisfactory. The developed method could be utilized for the determination and measurement of TCB and IVM in other samples.